2002
DOI: 10.1074/jbc.m110497200
|View full text |Cite
|
Sign up to set email alerts
|

Differential Characteristics and Subcellular Localization of Two Starch-branching Enzyme Isoforms Encoded by a Single Gene inPhaseolus vulgaris L.

Abstract: Starch-branching enzymes (SBE) have a dominant role for amylopectin structure as they define chain length and frequency of branch points. We have previously shown that one of the SBE isoforms of kidney bean (Phaseolus vulgaris L.), designated PvSBE2, has a molecular mass (82 kDa) significantly smaller than those reported for isologous SBEs from pea (SBEI), maize (BEIIb), and rice (RBE3). Additionally, in contrast to the dual location of the pea SBEI in both the soluble and starch granule fractions, PvSBE2 was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 42 publications
0
25
0
Order By: Relevance
“…These include reactivity toward various glucans including branched glucans (amylopectin and glycogen), amylose, and malto-oligosaccharides (MOS) (Tetlow 2012); chemicals such as cyclodextrins (Vikso-Nielsen and Blennow 1998), phosphorylated metabolites (Morell et al 1997), and citrate (Hamada et al , 2002; temperature dependence of activities Hamada et al 2002;Ohdan et al 2011;Sawada et al 2013); and association with starch granules (Rahman et al 1995;Mu-Forster et al 1996;Hamada et al 2001Hamada et al , 2002Grimaud et al 2008;Liu et al 2012b;Abe et al 2014). For other properties of BE, see review by Tetlow (2012).…”
Section: Structures and Basic Enzymatic Propertiesmentioning
confidence: 97%
See 1 more Smart Citation
“…These include reactivity toward various glucans including branched glucans (amylopectin and glycogen), amylose, and malto-oligosaccharides (MOS) (Tetlow 2012); chemicals such as cyclodextrins (Vikso-Nielsen and Blennow 1998), phosphorylated metabolites (Morell et al 1997), and citrate (Hamada et al , 2002; temperature dependence of activities Hamada et al 2002;Ohdan et al 2011;Sawada et al 2013); and association with starch granules (Rahman et al 1995;Mu-Forster et al 1996;Hamada et al 2001Hamada et al , 2002Grimaud et al 2008;Liu et al 2012b;Abe et al 2014). For other properties of BE, see review by Tetlow (2012).…”
Section: Structures and Basic Enzymatic Propertiesmentioning
confidence: 97%
“…Several reports showed that multiple forms of some enzymes such as SSI (Baba et al 1993) and BEIIa (Yamanouchi and Nakamura 1992) in rice endosperm, BEI in wheat endosperm (Båga et al 2000), and BEII from kidney bean (Hamada et al 2002) were generated from a single gene by transcriptional or posttranscriptional regulation and/or modification. However, the physiological significances of multiple forms of the same enzymes were unclear.…”
Section: Diversity Of Regulation Of Starch Biosynthesis Among Plant Smentioning
confidence: 99%
“…The low levels of BP2 expression throughout the plant suggested a potential role in processes other than meiosis, but its physiological significance remains unknown. Another example of AFE transcripts reported in plants is the SBE gene, which encodes a starch-branching enzyme (Hamada et al, 2002;Kitagawa et al, 2005). One shorter SBE transcript was expressed constitutively, while a longer transcript was expressed in limited tissues, including developing seeds.…”
Section: Discussionmentioning
confidence: 99%
“…Some enzymes of starch biosynthesis are found strongly associated with starch granules, including SBEII isoforms from a range of species (49)(50)(51)(52). The precise mechanism underlying the association of specific enzymes of starch synthesis with the starch granule are not known, although it has been suggested that alternative splicing of SBEII in bean (Phaseolus vulgaris L.) leads to partitioning within the starch granule (27). Recent evidence suggests that granule-associated proteins (including the SBEII class) become entrapped in the granule through association in heteromeric protein complexes (8,53).…”
Section: Tablementioning
confidence: 99%